2015
DOI: 10.5688/ajpe79453
|View full text |Cite
|
Sign up to set email alerts
|

Development and Assessment of the Multiple Mini-Interview in a School of Pharmacy Admissions Model

Abstract: Objective. To describe the development, implementation, and evaluation of the multiple mini-interview (MMI) within a doctor of pharmacy (PharmD) admissions model. Methods. Demographic data and academic indicators were collected for all candidates who participated in Candidates' Day (n5253), along with the score for each MMI station criteria (7 stations). A survey was administered to all candidates who completed the MMI, and another survey was administered to all interviewers to examine perceptions of the MMI. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…27 For these reasons, in the fall of 2013, the MMI was implemented in the UNC Eshelman School of Pharmacy admissions process. 32 …”
Section: Discussionmentioning
confidence: 99%
“…27 For these reasons, in the fall of 2013, the MMI was implemented in the UNC Eshelman School of Pharmacy admissions process. 32 …”
Section: Discussionmentioning
confidence: 99%
“…Schools are beginning to report including teamwork assessments as part of multiple mini-interview models, 8 but we could find no published reports of admissions that include an interprofessional assessment. Students who come into pharmacy based on their individual performance must be intentionally taught to value team performance.…”
mentioning
confidence: 95%
“…In addition to these academic measures, researchers have correlated behavioral/social qualities (sometimes referred to as "soft skills" or noncognitive qualities) including communication skills, empathy, ethical behavior and professionalism with outcomes in the PharmD curriculum 11 . These qualities are difficult to evaluate in standard or structured interviews, but can be assessed through the multiple-mini interview (MMI) 6,9,[16][17][18] . Recently, Heldenbrand et al showed that the MMI used during our admissions process is another tool that can be utilized to predict academic difficulty (previously defined as course grade of D, F, WF, course/year repetition, summer school, programmatic withdrawal or dismissal) in the didactic PharmD curriculum and therefore is an early identifier of academically at-risk students.…”
Section: A J P Ementioning
confidence: 99%